Paclitaxel‐Loaded Iron Oxide Nanoparticles for Targeted Breast Cancer Therapy. Issue 12 (7th November 2019) - Jeon, Mike; Lin, Guanyou; Stephen, Zachary R.; Kato, Frances L.; Zhang, Miqin
Abstract: Paclitaxel (PTX) is a potent drug for treating advanced solid carcinomas; however, its clinical utility is limited by its poor water solubility. Despite the promise of using nanoparticles to deliver hydrophobic PTX, achieving sufficient drug loading while maintaining small particle size and stability in biological media remains a challenge. Here, a PTX nanoparticle (NP) formulation with small size and great stability is presented that targets breast cancer cells and enables controlled release of PTX. This NP formulation (NP‐PTX‐FA) comprises a superparamagnetic iron oxide core coated with short‐ and long‐chain polyethylene glycol: the former for conjugation of hydrophobic PTX and folic acid (FA), and the latter as an outer layer for improved hydrophilicity. The NP‐PTX‐FA has a uniform size distribution (averaging 28.2 ± 0.64 nm) and high drug loading capacity of 22.8 wt% (vs <10 wt% normally). NP‐PTX‐FA releases the drug under conditions mimicking the acidic intracellular pH of breast cancer cells and the FA conjugation leads to higher NP uptake by target cells, enhancing the cytotoxicity to target cells compared to free PTX. This NP formulation holds great promise to improve breast cancer therapy and potential to deliver other hydrophobic drugs for treating various cancer types. Abstract : A nanoparticle that exhibits small particle size, great stability, high drug loading, and enables the controlled release of paclitaxel (PTX) for targeted treatment of breast cancer cells is developed. This targeted magnetic nanoparticle, functionalized with pH‐cleavable paclitaxel, significantly enhances the cytotoxicity toward tumor cells as compared to free paclitaxel.